Orientalist Discourse in Western Media Representations of Iran - Hossein Pirnajmoddin; Seyyed Mohammad Marandi; Mohamadreza Adeli (Taḥqīqāt-i Farhangī-i Īrān)
This paper addresses the representations of the Muslim world, especially Iran, in Western media. These representations are traced back in orientalist discourse, one through which ‘knowledge’ is produced about the East which empowers the West to justify and maintain its dominance over its Eastern Other. The writers first discuss the nature and functions of representation and proceed to examine some of the aspects and strategies of the Western media approach to the Muslim world in general and Iran in particular. The aim is to shed some light on the discursive functions and formations involved here. The need to address such pressing issues in order to create a more balanced and rational atmosphere necessary for a fruitful dialogue between nations and cultures is emphasized.